(untitled) (Research, Society and Development, 2023)
The present work aims to show, through a literature review, the immediate placement of implants, in order to understand the healing of extraction wounds and bone loss as well as various treatment resources that affect the biological response of bone and tissue. soft tissue compared to the delayed placement protocol. To this end, articles available in the following online databases were consulted: Virtual Health Library (VHL) which includes the databases SciELO (Scientific Electronic Library OnLine), Lilacs (Latin American and Caribbean Literature in Health Sciences), BENDEF E BIREME, published between 2018 and 2023, in Portuguese, English and Spanish. After searching the databases, the identified studies were archived and duplicate citations were eliminated to produce a list of all unique citations. The titles and summaries of these citations were then analyzed, and studies considered potentially eligible for inclusion in the review were selected for full reading. Thus, ten abstracts were selected from 135 titles in the initial search, and full texts were obtained. Therefore, only case studies were included in this review. Nevertheless, the review included studies of patients who required tooth extraction due to periapical infections, irrecoverable caries, trauma or periodontal disease. The present study concluded that immediate implants continue to be considered effective and safe treatments in the context of implant dentistry, in addition to meeting the patient’s aesthetic needs. Therefore, to obtain a necessary condition for the installation of the immediate implant with immediate loading to be possible, it is essential to evaluate the patient’s systemic condition, as well as high-quality clinical and radiographic examinations and good anamnesis, so that these elements end up supporting a good prognosis. It turns out that this procedure is still lacking in the public health system, that is, it is not accessible to the entire population.